(untitled) (Global Journal of Management and Business Research, 2024)
In order to meet their goals companies have always sought to be competitive exploiting natural resources as much as possible in order to generate more and more profits and consequently accumulate wealth and share it out among their shareholders This maximum exploitation of resources has led to changes in the environment putting humanity itself at risk through various natural disasters as well as social inequalities This has led various actors governments and civil society organizations to demand responsibility on the part of companies and Business Social Responsibility BSR has emerged among various terms with the aim of establishing measures that can enable sustainable development and has become an important ally for companies wishing to achieve success This research was therefore carried out with the aim of understanding what the practice of BSR consists of on the part of companies and what gains they make from this practice